Investigating the impact of artificial environmental watering on a semi‐arid, highly saline floodplain using electromagnetics and surface nuclear magnetic resonance. Issue 11 (2nd March 2020) - Li, Chris; Doble, Rebecca; Hatch, Michael; Heinson, Graham
Abstract: Floodplains have ecological and cultural significance and need to be managed properly. However, floodplains along the River Murray in South Australia are showing a substantial vegetation health decline due to increased salinization. To improve floodplain health, water resource managers are experimenting with the delivery of fresh water to the high priority floodplains. However, the salinity impact of watering on the shallow, saline groundwater is not well understood due to the presence of a spatially variable and impermeable surface clay layer. This study uses time‐domain electromagnetics (EM) and surface nuclear magnetic resonance (NMR) to assess the impact of watering on groundwater salinity in a South Australian River Murray floodplain. We examined the changes in bulk electrical conductivity (EC) from time‐domain EM data collected at five sites before and after a watering event. Only one site showed a bulk EC reduction of up to 5, 200 μS/cm, suggesting groundwater was freshened, whilst the remaining sites showed little change in bulk EC. Our results suggest the salinity impact of watering is highly localized and heterogeneous. For ecological management purposes, it is also desirable to estimate groundwater EC after watering. This study presents a method to estimate groundwater EC in a highly conductive environment by coupling EM with surface NMR. We also extended the analysis to an airborne‐EM survey to derive spatial distribution of groundwater EC, which provides additional insights into the floodplain processes and shows an overall good agreement with field observations. This study demonstrates the potential benefits of using geophysics to investigate floodplain dynamics. The methodology developed in this study is useful for first‐pass assessments of groundwater quality in a non‐invasive manner, which is transferrable to many other fresh or saline groundwater systems, especially in ecologically sensitive areas where traditional hydrogeological techniques may be unsuitable due to the potential disturbance of local ecosystems. Abstract : The impact of artificial watering on floodplain condition is evaluated using non‐invasive geophysical techniques of surface nuclear magnetic resonance and electromagnetics in a semi‐arid, highly saline environment.